Pendidikan Keagamaan Madrasah Diniyah Al Fatah - Abdul Azis Al Bone (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2006)
According to the law of national education system number 20 year 2003, religious education of madrasah diniyah is a part of national educational system. consequently, madrasah diniyah is not only fully as the responsibility of moslem community to establish, maintain, and develop, but it also a kind of the government’s responsibility and duty. historically, in the early existence, madrasah diniyah comes from-by and for the people. but, now, the government is legally demanded to manage madrasah diniyah in a parallel with the community’s aspiration and needs. this article tries to elaborate how people respond madrasah diniyah as the formal religious educational institution and how is the strategy for developing madrasah diniyah in line with the implementation of national education system law, number 20 year 2003. by taking case of madrasah diniyah al fatah, one of madrasah diniyah in demak, this article comes to conclusion that there are any situational responses to the issue of institutionalization of madrasah diniyah.